Acute rupture of a huge liver hydatid cysts in the peritoneal cavity causing an anaphylactic shock: A case report - Mohamed Zayati; Mohamed Ali Chaouch; Salem Mokni; Mohamed Maaref; Mehdi Abdelwahed; Hafeth Daly; Asma Ladib; Fethi Jebali; Aymen Kawech (Radiology Case Reports)
The rupture of hepatic hydatid cysts into the peritoneal cavity is an uncommon but life-threatening condition that can result in complications such as peritonitis and anaphylactic shock. This report describes the case of a 39-year-old diabetic male who presented with acute epigastric pain, fever (39°C), and abdominal rigidity. Imaging studies revealed pneumoperitoneum and the rupture of a large hepatic hydatid cyst measuring 20 × 30 cm located in the right lobe of the liver. Emergency laparotomy confirmed the rupture, and surgical management involved peritoneal lavage and initiation of antiparasitic therapy. The patient recovered fully and was discharged 23 days after surgery. Rupture of hepatic hydatid cysts occurs in only 1%-2% of cases and is often associated with large cyst size (>10 cm) and superficial location. Early imaging, particularly with CT, is crucial for diagnosis, while surgical intervention aims to manage the rupture, prevent further complications, and address residual cysts. This case highlights the significance of prompt diagnosis and management to avoid severe outcomes such as secondary peritoneal hydatidosis and anaphylactic shock.